RADICAL ISLAMISM IN ALGERIA: EVOLUTION AND CURRENT SITUATION - Silverio González, Yoslan (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2022)
The present article addresses radical Islamism in Algeria, encompassing the period between the rise and radicalization of the first Islamist groups, during the Civil War (1992-2002), and their activities in recent years. The study analyses aspects such as the tactics used by them, the rise of new groups and the fall of the old ones, as well as the impacts of these developments on the political scenario of Algeria.